2021
DOI: 10.1017/s0025315422000182
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgae from two coastal lagoons of the Gulf of California as indicators of heavy metal contamination by anthropogenic activities

Abstract: Metal concentrations in coastal zones are a critical study subject since anthropogenic activities surrounding these zones are increasing and affecting environmental concentrations of metals. Macroalgae have been used as biomonitors since they can act as indicators of metal concentrations in the water column. Tissue samples of three abundant macroalgae species (Spyridia filamentosa, Padina mexicana and Ulva ohnoi) were collected from three sites with different anthropogenic impacts at La Paz Bay and Guaymas Bay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
(142 reference statements)
0
0
0
Order By: Relevance
“…The anatomical distribution of the tumours was predominant in the anterior region of the body, like what is reported in other regions of the EP (Aguirre et al 1999;Reséndiz et al 2015), north Pacific (Work et al 2004) and Gulf of Mexico (Suárez-Domínguez et al 2020). It has been reported that the first signs of FP are the growth of small lesions in the anterior part of the body, and this could be explained by which suggests that could be incorporated into the diet of herbivorous animals, such as green turtles, representing a risk to their health (Riosmena-Rodríguez et al 2010;Mendez-Rodriguez et al 2021). Hence, the persistence of OCPs and heavy metals through the trophic web could represent a risk not only as a possible FP co-factor, but also for humans who feed on specimens with presence of these contaminants (Senko et al 2009).…”
Section: Pathology Of the Fp Tumoursmentioning
confidence: 73%
“…The anatomical distribution of the tumours was predominant in the anterior region of the body, like what is reported in other regions of the EP (Aguirre et al 1999;Reséndiz et al 2015), north Pacific (Work et al 2004) and Gulf of Mexico (Suárez-Domínguez et al 2020). It has been reported that the first signs of FP are the growth of small lesions in the anterior part of the body, and this could be explained by which suggests that could be incorporated into the diet of herbivorous animals, such as green turtles, representing a risk to their health (Riosmena-Rodríguez et al 2010;Mendez-Rodriguez et al 2021). Hence, the persistence of OCPs and heavy metals through the trophic web could represent a risk not only as a possible FP co-factor, but also for humans who feed on specimens with presence of these contaminants (Senko et al 2009).…”
Section: Pathology Of the Fp Tumoursmentioning
confidence: 73%
“…Macroalgae have a different ability to adapt to the environment. Environmental influences such as substrate, temperature, salinity, nutrients, water quality, and anthropogenic (community activities) will affect diverse species and even cause species damage [10,11,12].…”
Section: Introductionmentioning
confidence: 99%